2021
DOI: 10.21203/rs.3.rs-195847/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First-in-human AAV Gene Therapy for Tay-Sachs Disease

Abstract: Tay-Sachs Disease (TSD) is an inherited neurological disorder caused by deficiency of hexosaminidase A (HexA). Preclinical work demonstrated safety and efficacy of CNS gene therapy using AAVrh8-HEXA/HEXB. Here we describe an expanded access trial in two patients with infantile TSD (IND 18225). Case TSD-001 demonstrated neurodevelopmental regression by 8 months of age and severe seizures by 1 year was treated at 30 months. An equimolar mix of AAVrh8-HEXA and AAVrh8-HEXB (now AXO-AAV-GM2) was administered intrat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Indeed, AAVrh8-mediated gene therapy trials in Tay-Sachs sheep demonstrated safety and efficacy, with widespread vector distribution throughout the brain, as well as near normal levels of Hex A activity and attenuated ganglioside accumulation ( 19 ). This resulted in delayed onset of disease and increased life span in treated sheep and the initiation of a phase I clinical trial of the HEXA gene therapy product in January 2021 [ clinicaltrials.gov NCT04669535, ( 62 )].…”
Section: Naturally Occurring Sheep Disease Modelsmentioning
confidence: 99%
“…Indeed, AAVrh8-mediated gene therapy trials in Tay-Sachs sheep demonstrated safety and efficacy, with widespread vector distribution throughout the brain, as well as near normal levels of Hex A activity and attenuated ganglioside accumulation ( 19 ). This resulted in delayed onset of disease and increased life span in treated sheep and the initiation of a phase I clinical trial of the HEXA gene therapy product in January 2021 [ clinicaltrials.gov NCT04669535, ( 62 )].…”
Section: Naturally Occurring Sheep Disease Modelsmentioning
confidence: 99%
“…In contrast, systemic vector administration might be more susceptible to vector neutralization 34 . To address this problem, human gene therapy trials often include an immune suppression protocol to prevent a humoral and cellular immune response against AAV and the transgene 27,91,94 . Thus, it will remain a critical task to refine our understanding of gene therapy–associated immune response and its modulation while protecting patients from the risk associated with prolonged immune suppression.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, vector spread is limited compared with intravenous injection because distribution depends on interstitial, lymphatic, and axonal travel. However, certain conditions such as lysosomal storage diseases, e.g., TSD, undergo a mechanism called “cross‐correction,” which enables the distribution of the transgene from transduced to nontransduced cells and thus can achieve more comprehensive cellular correction than the spread of rAAV itself 27 . Another consideration is that the delivered volume is limited and might be restricted by the target brain region.…”
Section: Challengesmentioning
confidence: 99%
See 2 more Smart Citations